Inspiring IDEA: Girls on the Run’s developmental approach to and assessment of inclusion, diversity, equity, and access programming - Weiss, Maureen R.; Kipp, Lindsay E.; Riley, Allison (Frontiers in Psychology, 2023)
Introduction Evaluation studies of positive youth development (PYD) programs show promising impact on children’s psychosocial and behavioral outcomes, but less is known about how programming affects youth of varying racial, ethnic, and cultural identities. Girls on the Run, a physical activity-based PYD program, has developed curricula and coach training with a lens toward inclusion, diversity, equity, and access (IDEA). The purpose of this study was to assess the program’s effectiveness in achieving IDEA programming goals. Methods Surveys were completed by youth (n = 342), caregivers (n = 2,375), and coaches (n = 1,406), and focus groups/interviews were conducted with 12 youth, 20 caregivers, and 9 coaches, diverse in race, ethnicity, ability, and other identities. Survey and focus group/interview questions addressed participants’ thoughts and experiences regarding inclusion, diversity, equity, andaccess in Girls on the Run. Results Quantitative analyses of survey responses revealed favorable responses by all groups that the program: (a) provides a safe, inclusive, and supportive climate for all youth; (b) consists of teams with racially and ethnically diverse backgrounds; and, (c) successfully engages in strategies to reduce barriers to participation. Qualitative analyses of focus group/interview data resulted in 5 higher-order themes: (a) positive sentiments by girls, caregivers, and coaches; (b) social justice in the curriculum; (c) access to programming; (d) considerations regarding racial diversity; and, (e) serving gender-diverse participants. Discussion Collective findings characterized Girls on the Run as successful in meeting its pledge toward inclusion, diversity, equity, and access to participation. All groups recognized the program’s positive impact on girls’ social and emotional learning and fostering an atmosphere of community connectedness. Curricular lessons and coach training align with evidence based strategies for inclusive and equitable programming, which can serve as an exemplar for other out-of-school-time programs.